Degradation of fishing grounds in North Waters of Banten Province, Indonesia - Mario Limbong; Domu Simbolon; Ari Purbayanto; Roza Yusfiandayani; Khairul Amri (Depik, 2023)
The high level of fishing activity with small fishing vessels has resulted in relatively high utilization of marine space in coastal areas, manifesting changes in fishing grounds. Thus, this research aimed to analyze water quality, fishing intensity and to determine the level of degradation of fishing grounds in the northern waters of Banten Province. This research was conducted from June to August 2023 in the northern waters of Banten Province. Data collection was carried out using survey, remote sensing, and interview methods. Water quality data consisting of sea surface temperature, brightness, salinity, light attenuation coefficient, total suspended solids, and chlorophyll-a were analyzed descriptively. Eco-friendly capture fisheries data were taken directly from 120 fishermen and analyzed based on the CCRF criteria. Degradation status was determined by combining weight of water quality conditions and eco-friendly capture fisheries. Based on the research results, the northern waters of Banten Province is in good condition for biota life. Fishing equipment is dominated by eco-friendly fishing gear. Nevertheless, several parts of northern waters in Banten Province have experienced light degradation of fishing areas (18.28%) and the heavy degradation (7.71%). The use of marine space for capture fisheries in the northern waters of Banten Province is relatively high, around 50 units of fishing gear for 1 hectare of water.Keywords:EnvironmentFishing intensityFishing gearSpatial mappingWater quality